Voluntary Carbon Market in Local Community: Opportunities, Roles, and Linkages with Sustainable Tourism - Phaeophanchoo, Arun; Suveatwatanakul, Chokechai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article proposes the LEAF Model as an integrated conceptual framework for enhancing the capacity of local communities to participate in voluntary carbon markets. The model consists of four key components: 1) Local Empowerment, which focuses on strengthening community knowledge and capacity; 2) Emission Measurement, which emphasizes standardized measurement and reporting of greenhouse gas emission reductions; 3) Accreditation and Standardization, which facilitates access to credible certification systems and recognized standards; and 4) Fair Carbon Trade, which ensures transparent and equitable benefit-sharing mechanisms derived from carbon credits. Integrating the LEAF model into local policy frameworks and development planning—particularly in ecotourism destinations or communities with significant natural resource capital—can support the development of a green economy that effectively links greenhouse gas mitigation with the long-term sustainability of local communities.